2019
DOI: 10.1111/pbi.13140
|View full text |Cite
|
Sign up to set email alerts
|

A group VII ethylene response factor gene, ZmEREB180, coordinates waterlogging tolerance in maize seedlings

Abstract: SummaryGroup VII ethylene response factors (ERFVIIs) play important roles in ethylene signalling and plant responses to flooding. However, natural ERFVII variations in maize (ZmERFVIIs) that are directly associated with waterlogging tolerance have not been reported. Here, a candidate gene association analysis of the ZmERFVII gene family showed that a waterlogging‐responsive gene, ZmEREB180, was tightly associated with waterlogging tolerance. ZmEREB180 expression specifically responded to waterlogging and was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(76 citation statements)
references
References 89 publications
2
74
0
Order By: Relevance
“…The Arabidopsis AtRAP2.12 is a key transcriptional regulator of the core anaerobic response controlled hydraulic conductivity of root 1 (HCR1), thereby regulating hydraulic conductivity (Lpr) and hypoxia responsive genes hence modulating the resilience of plants to multiple flooding scenarios [143]. Similarly, ZmERFB180 [144] and TaERFVII.1 [145] conferred waterlogging tolerance in maize and wheat, respectively. Three ThRAP2.3/15/39 genes also played a vital role to cope with the waterlogging stress in the Taxodium hybrid [146].…”
Section: Function and Expression Pattern Of Ap2/erf Tfs Under Abioticmentioning
confidence: 99%
“…The Arabidopsis AtRAP2.12 is a key transcriptional regulator of the core anaerobic response controlled hydraulic conductivity of root 1 (HCR1), thereby regulating hydraulic conductivity (Lpr) and hypoxia responsive genes hence modulating the resilience of plants to multiple flooding scenarios [143]. Similarly, ZmERFB180 [144] and TaERFVII.1 [145] conferred waterlogging tolerance in maize and wheat, respectively. Three ThRAP2.3/15/39 genes also played a vital role to cope with the waterlogging stress in the Taxodium hybrid [146].…”
Section: Function and Expression Pattern Of Ap2/erf Tfs Under Abioticmentioning
confidence: 99%
“…Functioning as glutathione peroxidase and dehydroascorbate reductase (DHAR), plant GSTs can catalyze the reduction of hydroperoxides to less harmful alcohols and safeguard protein function from oxidative damage and maintain redox homeostasis by regenerating ascorbic acid from DHA [27]. Ethylene has an important role in the response of plants to biotic and abiotic stresses and is a major regulator of several waterlogging-adaptive plant traits, i.e., submergence-adaptive responses, resistance to hypoxia stress via an ethylene-controlled pathway, and formation of aerenchyma and adventitious roots [28]. The ethylene-responsive element binding factor (ERF) proteins are key transcriptional regulators in response to diverse biotic and abiotic stresses in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Seeds of maize inbred line B73 were planted in a greenhouse with a controlled temperature (~28 • C/22 • C day/light cycle), a 14 h/10 h light/dark cycle (light time: 7:00 am-9:00 pm), and average humidity (60% average). The growth substrate and waterlogging treatments were conducted as previously described in [46]. Briefly, ten uniform seedlings were planted in a plastic pot, and treatments were applied by maintaining a 2-3 cm water layer above the substrate at the second leaf stage, and stress was treated at 8:00 am.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Investigations in plants have shown that group VII AP2-EREBP genes control flooding response and low-oxygen tolerance [62]. Of the 19 group VII AP2-EREBP genes in maize [46], eight genes were significantly up-regulated, implying that their potential functions regulate hypoxia response. These data demonstrated the discrepant performance of TFs under WS conditions.…”
Section: Differential Response Of the Transcription Factor Families Imentioning
confidence: 99%